2021
DOI: 10.1097/md.0000000000026843
|View full text |Cite
|
Sign up to set email alerts
|

Biologic therapy for amyloid A amyloidosis secondary to rheumatoid arthritis treated with interleukin 6 therapy

Abstract: Introduction: Secondary amyloidosis is a rare complication of rheumatoid arthritis (RA) that is histologically characterized by the deposition of amyloid fibrils in target organs, such as the kidneys and gastrointestinal tract. Controlling the inflammatory response is essential to prevent organ dysfunction in amyloid A (AA) amyloidosis secondary to RA, and no clear treatment strategy exists. Patient Concerns and Diagnosis: A 66-year-old woman with RA, who had been treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
2
0
2
Order By: Relevance
“…Todos disminuyeron los reactantes de fase aguda y la proteinuria. Un informe de caso más reciente de Ju-Yang Jung y col. mostró respuesta clínica gastrointestinal y articular durante el tratamiento con tocilizumab en una paciente con artritis reumatoide complicada con amiloidosis AA 16 .…”
Section: Discussionunclassified
“…Todos disminuyeron los reactantes de fase aguda y la proteinuria. Un informe de caso más reciente de Ju-Yang Jung y col. mostró respuesta clínica gastrointestinal y articular durante el tratamiento con tocilizumab en una paciente con artritis reumatoide complicada con amiloidosis AA 16 .…”
Section: Discussionunclassified
“…112 In serial studies, IL-6 inhibitors were reported to be effective in terms of inhibiting the development and progression of renal amyloidosis, 113 including in patients with RA. 114 IL-6 inhibitors are believed to be relatively safe in patients with RA and interstitial lung diseases 115 and demyelinating diseases. 116 In addition, there are data on tocilizumab efficacy in patients with optic neuromyelitis 117 and systemic sclerosis-associated interstitial lung touchREVIEWS in RMD disease, 118,119 with the latter resulting in tocilizumab receiving approval by the US Food and Drug Administration for these patients.…”
Section: Safety Considerations For the Interleukin 6 Inhibitors As A ...mentioning
confidence: 99%
“…У пациентов с РА, страдающих почечной недостаточностью, на фоне лечения ингибиторами ИЛ-6 увеличения риска НЛР или ухудшения функции почек не наблюдается [105]. Отмечена определенная эффективность ингибиторов ИЛ-6 в отношении развития и прогрессирования амилоидоза почек [106], в том числе при РА [107].…”
Section: таблица 6 сравнительная эффективность терапии ингибиторами и...unclassified